Д. І. Багалій: Шлях золотої середини (до 140-річчя з дня народження) - Кравченко, В. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
SUMMARY Kravchenko V.V. D.I. Bagaliy: the Route of the Golden Mean (for the 140-th birthday) The paper deals with one of outstanding Ukrainian historians of the late 19th and the beginning of the 20th centuries D. I. Bahalij. The role of scientist in the Ukrainian cultural and national revival is described. Particular attention is devoted to some unknown aspects of his biography. The author illuminated relations of D. I. Bahalij with the main representatives of the Ukrainian cultural and political process.